A world Of Politics - FERGUSEN, Yale H (Rautledge, 2008)
Yale H. Ferguson and Richard W. Mansbach have made a significant contribution to our contemporary understanding of global politics. This collection contains some of their classic essays and many unpublished articles which have been edited into a coherent and stimulating collection.